2017
DOI: 10.1016/j.toxrep.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

UVB damage onset and progression 24 h post exposure in human-derived skin cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…The oxidative stress induced by UVB is also involved in the activation of the intrinsic apoptotic signaling pathway [30]. Our data showed that excessive ROS levels, especially H 2 O 2 , associated with a decrease of the endogenous antioxidant system induced by UVB on L929 cells, caused the loss of Δ ψ m, and significantly activated caspase 9, as observed by western blotting assays.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The oxidative stress induced by UVB is also involved in the activation of the intrinsic apoptotic signaling pathway [30]. Our data showed that excessive ROS levels, especially H 2 O 2 , associated with a decrease of the endogenous antioxidant system induced by UVB on L929 cells, caused the loss of Δ ψ m, and significantly activated caspase 9, as observed by western blotting assays.…”
Section: Discussionsupporting
confidence: 60%
“…The MAPK signaling pathway is activated by large amounts of ROS produced in cells irradiated with UVB, followed by downstream transcription factor phosphorylation, leading to the expression of apoptotic factors and MMPs [5, 30]. Since DHCA reduces apoptosis and MMP expression, we intended to verify whether DHCA may act by inhibiting phosphorylation of the MAPK subfamilies JNK and p38 (Figure 7(b)).…”
Section: Resultsmentioning
confidence: 99%
“…61 Many signaling pathways are involved, including p53-mediated activation of pro-apoptotic factors as a result of DNA double-stranded breaks, MAP-kinase activation, and the capacity for DNA repair. [62][63][64] It was previously demonstrated that Ru(II) anticancer drugs can trigger DNA damage which in turn activates apoptosis via the intrinsic pathway. 65 Zhang and coworkers reported the intercalative potential of Ru(II) polypyridyl complexes which were shown to induce apoptosis in A549 cells, as concluded from ow cytometric studies.…”
Section: Resultsmentioning
confidence: 99%
“…UVA is absorbed by chromophores in dermal cells to induce the generation of ROS that indirectly cause oxidative damage to DNA, leading to mutations and cancer (Farrar et al, 2018;Rybchyn et al, 2018). In contrast, UVB damages the membranes and proteins of cells on the surface layer of skin and superficial layer of the dermis, leading to sunburn erythema that can result in skin cancer in extreme cases (Khalil and Shebaby, 2017;Raad et al, 2017). ROS can activate the expression of MMPs that degrade the extracellular matrix including collagen and elastin fibers in the dermis, which can cause wrinkles, dandruff, and dullness (Burnstock et al, 2012;Ryu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%